2022
DOI: 10.3390/en16010056
|View full text |Cite
|
Sign up to set email alerts
|

Granulates Based on Bio and Industrial Waste and Biochar in a Sustainable Economy

Abstract: This review presents the latest research works detailing granulation processes and granulates, including and based on waste (bio and industrial) as a biofuel/energy source and the possible usage of granulates from and/or based on biochar. The innovative aspect is that the article focuses on the broadest possible environmental aspect understood in minimizing the burden related to the amount and composition of waste generated by various industries. The aim of the study is to demonstrate the processes as an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Additionally, various researchers have shown that pelleting can provide effective solutions to various challenges in today's world, aligning with the goals of a sustainable economy. It is also worth noting that pelleting processes use readily available raw materials and additives, such as mineral fillers or water, making the entire operation relatively easy, waste-free, and profitable [17].…”
Section: Economical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, various researchers have shown that pelleting can provide effective solutions to various challenges in today's world, aligning with the goals of a sustainable economy. It is also worth noting that pelleting processes use readily available raw materials and additives, such as mineral fillers or water, making the entire operation relatively easy, waste-free, and profitable [17].…”
Section: Economical Evaluationmentioning
confidence: 99%
“…A study conducted by Rostocki et al [17] demonstrated that pelleting through pressure agglomeration is an effective method for processing waste materials generated by various industries. Research has also been carried out on the compaction of various food production wastes for their reuse as solid biofuels [18], animal feed [19], or fertilizers [5].…”
Section: Introductionmentioning
confidence: 99%
“…The calorific value of the obtained solid fraction increases with the temperature of the process. It is the result of increasing the concentration of carbon in the product [ 35 , 36 , 37 ]. In the first phase of the pyrolysis process, taking place at low temperatures of 250–350 °C, carbon monoxide and carbon dioxide are released from the biomass, reducing the oxygen concentration in the biomass, which component in the fuel lowers its calorific value.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, thanks to the use of SHS for torrefaction processes, it is possible to recover by-products and at the same time valuable products, such as, for example, formic acid and acetic acid. This method, thanks to the cessation of the combustion of products and the optimization of obtaining plant, forest and agricultural biomass, leads to a positive impact on the quality of environmental performance 40 . Economic profitability depends on the use of low-temperature waste heat for pre-drying the biomass and the use of steam instead of other gases such as fossil fuels or gases generated during the torrefaction process, the so-called "Torgas" 41 44 .…”
Section: Introductionmentioning
confidence: 99%